2017
DOI: 10.1186/s12879-017-2817-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of naturally occurring NS5A resistance-associated substitutions in patients infected with hepatitis C virus subtype 1a, 1b, and 3a, co-infected or not with HIV in Brazil

Abstract: BackgroundNon-structural 5A protein (NS5A) resistance-associated substitutions (RASs) have been identified in patients infected with hepatitis C virus (HCV), even prior to exposure to direct-acting antiviral agents (DAAs). Selection for these variants occurs rapidly during treatment and, in some cases, leads to antiviral treatment failure. DAAs are currently the standard of care for hepatitis C treatment in many parts of the world. Nevertheless, in Brazil, the prevalence of pre-existing NS5A RASs is largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
23
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 41 publications
(51 reference statements)
8
23
1
2
Order By: Relevance
“…Among the positions analyzed for NS5A, the L31M and Y93H ones have been evaluated as relevant resistance mutations since their baseline presence significantly affects DAA treatment outcomes . In the present study, the prevalence of L31M (6.7%) seemed to be higher than the one observed by most researchers, who found a prevalence around 0%‐5% . On the contrary, the frequency of Y93H (2.3%) did not reach the prevalence reported in Asiatic countries (10%‐19%) but was similar to that observed in studies carried out in Brazil .…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Among the positions analyzed for NS5A, the L31M and Y93H ones have been evaluated as relevant resistance mutations since their baseline presence significantly affects DAA treatment outcomes . In the present study, the prevalence of L31M (6.7%) seemed to be higher than the one observed by most researchers, who found a prevalence around 0%‐5% . On the contrary, the frequency of Y93H (2.3%) did not reach the prevalence reported in Asiatic countries (10%‐19%) but was similar to that observed in studies carried out in Brazil .…”
Section: Discussionsupporting
confidence: 74%
“…Contrary to expectations, findings from this study show a similar prevalence of NS5A RASs in patients infected with HCV‐1a and HCV‐1b. Most previous studies report a higher NS5A RASs prevalence in HCV‐1b infected patients; other studies from Brazil had shown similar prevalence in both subtypes or even higher in HCV‐1a …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The presence of substitutions conferring resistance to NS5A inhibitors has been widely reported both in therapy-naïve and in relapser patients from Europe [ 10 , 33 , 35 38 ], USA [ 37 , 39 , 40 ], and Asia [ 41 43 ]. However, NS5A sequences from South America are poorly analyzed yet [ 9 , 44 ]. Recent studies have revealed that the mean prevalence of NS5A genotype 1 baseline RASs to different inhibitors ranges from 6% to 16% using population sequencing or deep sequencing [ 27 , 37 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo de vida real francês, que avaliou a efetividade do uso de SOF e DCV em 768 pacientes com genótipo 1, 95% dos pacientes alcançaram RVS12. Este estudo também demonstrou que a duração ideal do tratamento para pacientes não cirróticos é de 12 semanas e para pacientes cirróticos é de 24 semanas (POL et al, 2017 apresentavam tais mutações, sendo as mais frequentemente descritas M28V e Q30H/R; enquanto 6,0% dos pacientes genótipo 1b as apresentava, com predominância de L31F/V e Y93H (MALTA et al, 2017). Em nosso estudo observamos somente a mutação Y93H em dois dos pacientes testados.…”
Section: Sof 1 + DCV 2 (N = 130) Sof + Smv 3 (N = 132)unclassified